2013
DOI: 10.1021/jf4006033
|View full text |Cite
|
Sign up to set email alerts
|

Maize Kernel Antioxidants and Their Potential Involvement in Fusarium Ear Rot Resistance

Abstract: The potential involvement of antioxidants (α-tocopherol, lutein, zeaxanthin, β-carotene, and ferulic acid) in the resistance of maize varieties to Fusarium ear rot was the focus of this study. These antioxidants were present in all maize kernel stages, indicating that the fumonisin-producing fungi (mainly Fusarium verticillioides and Fusarium proliferatum ) are likely to face them during ear colonization. The effect of these compounds on fumonisin biosynthesis was studied in F. verticillioides liquid cultures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 46 publications
2
68
0
Order By: Relevance
“…) and other natural products (Picot et al . ). The high lipophilicity of a natural product favours its entry into the fungal cell where it might act on physiological modulators of mycotoxin biosynthesis or on signal transduction pathways upstream of the biosynthetic pathway (Holmes et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and other natural products (Picot et al . ). The high lipophilicity of a natural product favours its entry into the fungal cell where it might act on physiological modulators of mycotoxin biosynthesis or on signal transduction pathways upstream of the biosynthetic pathway (Holmes et al .…”
Section: Discussionmentioning
confidence: 97%
“…The reasons for the observed inhibitions, however, could not be elucidated. Previous studies report that the increase in lipophilicity enhances the fungistatic (Guiraud et al 1995), and antifumonisin activities of phenolic compounds (Dambolena et al 2011) and other natural products (Picot et al 2013). The high lipophilicity of a natural product favours its entry into the fungal cell where it might act on physiological modulators of mycotoxin biosynthesis or on signal transduction pathways upstream of the biosynthetic pathway (Holmes et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The pigmented pericarp expressed by the P1‐rr genotype was composed of several flavonoid compounds and antioxidants that are involved in resistance to maize fusarium diseases (Picot et al ., ; Sampietro et al ., ; Santiago et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that in the earliest phase of kernel development of two yellow corn hybrids, chlorogenic acid may play a role in corn resistance to red ear rot and DON accumulation (Atanasova‐Penichon et al 2012). In addition, a possible role of cell wall‐bound ferulic acid in corn resistance to F. verticillioides was suggested (Picot et al 2013). To date no report has analyzed the evolution of phenolic acids at different stages of kernel development and their role in the resistance to mycotoxin accumulation in corn genotypes characterized by a wide array of kernel traits.…”
mentioning
confidence: 99%